The Acute Phase of Trypanosoma cruzi Infection Is Attenuated in 5-Lipoxygenase-Deficient Mice. (3rd August 2014) - Canavaci, Adriana M. C.; Sorgi, Carlos A.; Martins, Vicente P.; Morais, Fabiana R.; de Sousa, Érika V. G.; Trindade, Bruno C.; Cunha, Fernando Q.; Rossi, Marcos A.; Aronoff, David M.; Faccioli, Lúcia H.; Nomizo, Auro
Abstract : In the present work we examine the contribution of 5-lipoxygenase- (5-LO-) derived lipid mediators to immune responses during the acute phase of Trypanosoma cruzi infection in 5-LO gene knockout (5-LO −/− ) mice and wild-type (WT) mice. Compared with WT mice, the 5-LO −/− mice developed less parasitemia/tissue parasitism, less inflammatory cell infiltrates, and a lower mortality. This resistance of 5-LO −/− mice correlated with several differences in the immune response to infection, including reduced PGE2 synthesis; sustained capacity of splenocytes to produce high levels of interleukin (IL)-12 early in the infection; enhanced splenocyte production of IL-1 β, IL-6, and IFN- γ ; rapid T-cell polarization to secrete high quantities of IFN- γ and low quantities of IL-10; and greater numbers of CD8 + C D 4 4 h i g h C D 62 L l o w memory effector T cells at the end of the acute phase of infection. The high mortality in WT mice was associated with increased production of LTB4 /LTC4, T cell bias to produce IFN- γ, high levels of serum nitrite, and marked protein extravasation into the peritoneal cavity, although survival was improved by treatment with a cys-LT receptor 1 antagonist. These data also provide evidence that 5-LO-derived mediators negatively affect host survival during the acute phase of T. cruzi infection.